Internet psychotherapeutic interventions for anxiety disorders—A critical evaluation - Bandelow, Borwin; Wedekind, Dirk (BMC Psychiatry, 2022)
Background: During the COVID-19 pandemic, internet-delivered psychotherapeutic interventions (IPI) move increasingly into the focus of attention. Method: We reviewed 39 randomized controlled studies of IPIs with 97 study arms (n = 4122 patients) for anxiety disorders (panic disorder/agoraphobia, generalized anxiety disorder, and social anxiety disorder) and performed a meta-analysis. Most studies were conducted with cognitive behavioural approaches (iCBT). Results were compared with a previous meta-analysis examining medications and face-to-face (F2F) psychotherapy. Results: In direct comparisons, IPIs were as effective as F2F-CBT and superior to waitlist controls. Programs with more intensive therapist contact yielded higher effect sizes (ES).We compared the obtained ES with a previous comprehensive meta-analysis of 234 studies. In this comparison, iCBT was less effective than individual F2F-CBT and medications, not different from pill placebos, and more effective than psychological placebo and waitlist (p > .0001 for all comparisons).ES of IPIs may be overestimated. Treatments were only compared to waitlist, which is not a sufficient control condition. 97% of the studies were not blinded with regard to the main outcome measure. 32% of the participants received antianxiety drugs during the trials. In 89%, participants were recruited by advertisements rather than from clinical settings, and 63% of the participants had an academic background (students or university employees) which might affect the generalizability of the findings.Remote diagnoses were often made by students without completed training in psychotherapy. In only 15% of the studies, diagnoses were made in personal contact with a psychiatrist or psychologist. In 44% of the studies, the ‘therapists’ maintaining remote contact with the participants were mostly students without completed psychotherapy education. Conclusions: IPIs may be a useful tool when face-to-face psychotherapy is not easily available, or as an add-on to standard psychotherapeutic or psychopharmacological treatments but should perhaps not be used as monotherapy. We have suggested standards for future research and the practical use of IPIs. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Agoraphobia; Anxiety; Anxiety Disorders; COVID-19; Generalized Anxiety Disorder; Humans; Internet; Intervention; Pandemics; Panic Disorder; Psychotherapy; Randomized Controlled Trials as Topic; Social Phobia; Treatment Outcome; anxiety disorders; generalised anxiety disorder; internet psychotherapy; meta-analysis; panic disorder; social anxiety disorder